The Legal–Security Paradox of Green Extractivism: A Green Criminology Inquiry into Corporate Roles and Counterterrorism Implications in Indonesia: Paradoks Hukum-Keamanan dalam Ekstraktivisme Hijau: Kajian Kriminologi Hijau mengenai Peran Korporasi dan Implikasinya terhadap Pemberantasan Terorisme di Indonesia - Venessa Huwae; Sudrajat Tedi; Tri Lisiani Prihatinah; Duhita Pandya; Dede Indraswara (Universitas Negeri Semarang, 2026)
This article critically examines the structural incapacity of Indonesian law to anticipate and regulate the transformation of natural resource exploitation into vectors of national security risk. Operating within the normative-doctrinal tradition, the study adopts statute, conceptual, and case-based legal approaches to interrogate the triadic relationship between corporate actors, ecological destruction, and political violence. The central argument advanced is that Indonesian law sustains a paradox: it simultaneously authorises resource extraction as a developmental imperative while failing to acknowledge that extractivism generates structural grievances which may radicalise affected communities, thereby constituting a pre-terrorism environment. Green criminology serves as the analytical framework, augmented by ecological justice theory, Rawlsian distributive philosophy, and Critical Legal Studies. Doctrinal analysis reveals that the Mineral and Coal Mining Law (UU Minerba), the Environmental Protection and Management Law (UUPPLH), and the Anti-Terrorism Law (UU Terorisme) operate in regulatory silos, producing normative gaps through which corporations escape accountability for harms that transcend environmental categories and enter the domain of human-ecological security threats. Case analysis of PT. Kallista Alam, PT. Adei Plantation, and related litigation demonstrates that courts have yet to articulate a jurisprudential framework linking corporate environmental crime to security consequences. This article concludes by proposing a 'Green Security Law Framework' an integrated normative architecture reconciling environmental, security, and counterterrorism law as the prescriptive response to a legal deficit that renders the Indonesian state structurally complicit in its own security vulnerabilities.